Determinación de parásitos intestinales en gallinas criollas en la zona rural del Recinto Pijullo del Cantón Urdaneta - Jaén Álava, Dayler Jeremi (2024)
Parasites usually affect birds in all their stages, due to their predatory action, they are more prone to damage young birds and in their laying stage due to the expoliatriz effect (Mancheno, 2023), that is why I saw the need to conduct a study to evaluate the presence of intestinal parasites in birds in the rural area of Pijullo of the Urdaneta Canton, with the objective of educating the community through a database. On the negative and positive effects of their poultry farms. For the realization of this research we take into account the considerable amount of parasites that exist in animals, in my case the birds, thus leading us to consider investigating more on the subject in order to know how frequent are these parasites in birds and why they appear. The purpose of this research work is the identification of intestinal parasites in Creole hens in the rural area of the Pijullo precinct of the Urdaneta canton. For this purpose, an experimental approach was carried out. Since the variables are manipulated, it is also a study through the analysis of this research and the data collected with a purpose. The procedure consists of taking fresh fecal samples from the birds in the morning and taking them to the laboratory for coprological examination, while conducting an epidemiological study of Creole hens, taking into account three variables: deworming, housing and presence of other animals. The age of the animals under study was categorized in 3 groups, animals from 6 to 7 months with 20 birds, 4 of which were positive for intestinal parasites, representing 43%. Animals from 7 to 8 months with 30 birds, of which 3 were positive, representing 32%, and animals from 8 to 9 months with 20 birds, of which 2 were positive, representing 22%. In terms of sex, the greatest number of test subjects in the present investigation were females, 51 animals (73%) and 19 males (27%).